Steady-state Characterization of Particle Number Emissions from a Heavy-Duty Euro VI Engine Fueled with Compressed Natural Gas. (August 2018) - Distaso, E.; Amirante, R.; Tamburrano, P.; Reitz, R.D.
Abstract: The objective of the present work is to provide an exhaustive characterization of size distributions and number density of the particles emitted from a modern EURO-VI heavy-duty 4-cylinder engine, fueled with compressed natural gas. To achieve this goal, a wide range of operating conditions (for a total of 60 operating points) were investigated during the experimental campaign. Namely, the engine speed was varied from 800 to 3500 rpm and the engine load ranged from 20 to 100% of the full-load condition. Steady-state and stoichiometric conditions were ensured during the tests. The data were collected by using two particle sample devices, located at two distinct sampling points. In particular, samples were simultaneously collected directly from the exhaust pipe, upstream of the Three-Way Catalyst (TWC) and from an exhaust gas dilution system (CVS). In the first case, a fast-response particle size spectrometer (DMS500) was employed, while a condensation particle counter (APC489) was used in the second case. The experimental approach used in the present work allowed the identification of the correlations linking the main engine working parameters with the emitted particle levels of the tested natural gas engine. Furthermore, the use of two sampling devices located in two different positions along the exhaust stream, allowed to highlight the effects that the TWC and the dilution tunnel can produce on particulate emissions. The reported results provide more insight on the particle emission process related to natural gas engines.